Karakteristik Fisikokimia Kopi Lelesan Terhadap Suhu Seduhan dan Lama Ekstraksi. - Lukmanul nul hakim (Universitas Serambi Mekkah, 2021)
Lelesan coffee is physiologically has experienced perfect maturation naturally, so it will fall due to late picking. Coffee is a non alcoholic plant and also belongs to the category of refreshing drinks. Coffee as a refreshing drink contains more antioxidants than tea and chocolate. The mainstay content in lelesan coffee in addition to caffeine, there is also a juice content. The juice content is the solubility of a substance in organic solvents caused by heating and steeping. The purpose of this study was to examine the effect of steeping temperature and extraction time on the physicochemical properties of lelesan coffee (Coffea arabica). This study used a 2 factorial completely randomized design (CRD) consisting of steeping temperature, A1: 85°C, A2 : 95°C, A3 : 105°C and extraction time, B1 = 5 minutes, B2 = 10 minutes, B3 = 15. The observed variables were water content, juice content and organoleptic test of taste and color. The best treatment for coffee extract was obtained at a steeping temperature of 85 oC and extraction time of 10 minutes (A1B2) with the value of each parameter, namely juice content 23.43%, taste organoleptic test 4.12 (like), color 4.12 ( like).